Monumental Seattle : The Stories Behind the City's Statues, Memorials, and Markers - Spalding, Robert, 1968- (Book collections on Project MUSE., 2018)
"A guide to the statues, plaques, and memorial markers in Seattle, Washington."--Provided by publisher.